2016
DOI: 10.1016/j.ejvs.2015.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Bone Like Arterial Calcification in Femoral Atherosclerotic Lesions: Prevalence and Role of Osteoprotegerin and Pericytes

Abstract: These results suggest that bone like arterial calcification (OM) is highly prevalent at femoral level. Pericyte cells and the OPG/RANK/RANKL triad seem to be critical to the formation of this ectopic osteoid tissue and represent interesting potential therapeutic targets to reduce the clinical impact of arterial calcification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 29 publications
1
38
2
1
Order By: Relevance
“…Downregulated genes were mainly involved in cytoskeleton organization, cellular component organization, and positive regulation of cellular process and confirm the recent findings [ 15 17 ] ( Table 3 ). Besides, as shown in Table 4 , the KEGG analysis showed that upregulated genes participate in osteoclast differentiation [ 18 20 ], cytokine-cytokine receptor interaction [ 21 ], and chemokine signaling pathway [ 22 24 ]. Downregulated genes took part in focal adhesion [ 25 27 ], regulation of actin cytoskeleton [ 27 29 ], and arrhythmogenic right ventricular cardiomyopathy (ARVC) [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Downregulated genes were mainly involved in cytoskeleton organization, cellular component organization, and positive regulation of cellular process and confirm the recent findings [ 15 17 ] ( Table 3 ). Besides, as shown in Table 4 , the KEGG analysis showed that upregulated genes participate in osteoclast differentiation [ 18 20 ], cytokine-cytokine receptor interaction [ 21 ], and chemokine signaling pathway [ 22 24 ]. Downregulated genes took part in focal adhesion [ 25 27 ], regulation of actin cytoskeleton [ 27 29 ], and arrhythmogenic right ventricular cardiomyopathy (ARVC) [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Only data from a single‐center retrospective study by Stavroulakis et al found the 1‐year primary patency of DCB in CFA disease to be 68% and a TLR rate of 25% . The limited efficacy was primarily attributed to high rates of osteoid metaplasia and heavy calcifications found in CFA atherosclerotic plaques, which may prove to be more amenable to debulking strategies …”
Section: Endovascular Therapies To Cfa Disease and Evidence For Theirmentioning
confidence: 99%
“…In addition, a significant difference in the rate of failure following CFA reconstruction was noted from BASI, with six cases of stent failure due to CFA occlusion, compared to no events for CFE ( P = 0.02). The role of bioabsorbable stents in atherosclerotic CFA occlusive disease appears initially to be limited, as bioabsorbable stents lack the radial force for heavily calcified lesions in the CFA typified by osteoid metaplasia, though further randomized trials are needed …”
Section: Further Endovascular Intervention and Trials In Cfa Therapymentioning
confidence: 99%
“…Despite being exposed to similar risk factors, peripheral arteries develop heterogeneous atherosclerotic lesions. Our previous work showed that carotid arteries develop predominantly lipid-rich lesions and microcalcifications, while femoral arteries develop fibrotic lesions, with extensive vascular calcification (VC) and frequent presence of osteoid tissue (1)(2)(3)(4). These differences may have major clinical implications.…”
Section: Introductionmentioning
confidence: 99%